Low-dose, 128-slice, dual-source CT coronary angiography: accuracy and radiation dose of the high-pitch and the step-and-shoot mode. Issue 12 (10th June 2010) - Alkadhi, Hatem; Stolzmann, Paul; Desbiolles, Lotus; Baumueller, Stephan; Goetti, Robert; Plass, Andre; Scheffel, Hans; Feuchtner, Gudrun; Falk, Volkmar; Marincek, Borut; Leschka, Sebastian
Abstract : Objective: To compare the diagnostic accuracy and radiation doses of two low-dose protocols for coronary artery imaging with second-generation, dual-source CT in comparison with catheter angiography (CA). Design, setting and patients: Prospective, single-centre study conducted in a referral centre enrolling 100 patients with low-to-intermediate risk and suspicion of coronary artery disease. All patients underwent contrast-enhanced, 128-slice, dual-source CT coronary angiography and CA. Patients were randomly assigned to two different low-dose CT protocols (each 100 kV/320 mA): in group A (n=50), CT was performed using the prospectively electrocardiography (ECG)-gated step-and-shoot (SAS) mode; in group B (n=50), CT was performed using the prospectively ECG-gated high-pitch mode (pitch 3.4). The image quality and presence or absence of significant coronary stenosis in all coronary segments were evaluated by two blinded and independent observers. CA served as the standard of reference. Results: Sixty-one significant stenoses were found in group A, and 69 in group B. There was no significant difference in age (group A, 62±8yrs; group B, 63±8yrs; p=0.72), body mass index (group A, 26.4±3.1kg/m2; group B, 25.9±2.8kg/m2; p=0.41) and heart rate (HR) (group A, 58±8bpm; group B, 56±10bpm; p=0.66) between the groups. Diagnostic image quality was obtained in 98.6% (651/660) of segments in group A and in 98.9% (642/649) in group B, with no significant differences between groups. Sensitivity, specificity and positive and negative predictive values were 94%, 91%, 85% and 97% per-patient in group A, and 93%, 94%, 89% and 97% per-patient in group B (no significant differences). The effective radiation dose in group B (0.9±0.1 mSv) was significantly (p<0.01) lower than that in group A (1.4±0.4 mSv). Conclusions: Both the high-pitch and the SAS mode for low-dose CT coronary angiography provide high accuracy for the assessment of significant coronary stenoses, while the high-pitch mode further significantly lowers the radiation dose.